Características do teletrabalho e síndrome de burnout em professores da educação básica durante a pandemia da Covid-19 - Coelho, Elenise Abreu (2022)
Emergency Remote Teaching, adopted to enable the continuity of educational activities in the face of measures to combat the spread of the COVID-19 virus, caused a series of changes in the characteristics of teaching, due to the imposition of telework. This scenario contributed to the worsening of the mental health conditions of teachers, who constitute one of the professional categories most affected by occupational diseases. Therefore, this study aimed to evaluate the relationship between the characteristics of telework and Burnout syndrome in elementary school teachers in the State of Rio Grande do Sul during the COVID-19 pandemic. For that, three studies were carried out. In study 1, the method adopted was the narrative review of literature, through the construction of a theoretical-analytical framework, publications on the structural aspects of teaching in basic education, considering sociohistorical, political and economic events, and recent studies, published from 2020, which relate the pandemic aspects and teaching. Studies 2 and 3, with a quantitative, transversal and correlational method, resulted from an online survey, in which 304 teachers of basic education in Rio Grande do Sul participated. Teachers answered a sociodemographic data questionnaire, the Cuestionario para la Evaluación del Síndrome de Quemarse por el Trabajo (CESQT) and the Work Design Questionnaire (WDQ). Data derived from empirical studies were subjected to descriptive statistics, Spearmann correlation analyses, and Mann Whitney and Kruskall Wallis U tests for comparison by groups. From Study 1, organizational factors at a macrosocial level were identified, which threaten the physical and emotional well-being of teachers in carrying out their work, and which intensified with the changes imposed by the COVID-19 pandemic. The results of Studies 2 and 3 indicated a negative perception of teachers in relation to the characteristics of their work context, higher levels of burnout in teachers who already had a diagnosis of mental disorder, and differences in the perceptions of work characteristics and burnout levels, among teachers working in early childhood education and in the final years of elementary and high school. Correlations were identified between the characteristics of work and the dimensions of Burnout Syndrome. It is concluded that interventions aimed at promoting mental health in teaching are necessary, which will only be effective from changes in the organization of work, considering the characteristics and specificities of each performance context and level of education.